P422 Transition from intravenous to subcutaneous infliximab and vedolizumab: adherence, satisfaction and safety profile in a cohort of patients with Inflammatory Bowel Disease. (30th January 2023) - Todeschini, A; Geccherle, A; Signoretto, P; Fasoli, E; Variola, A
Abstract: Background: Inflammatory Bowel Disease (IBD), Ulcerative Colitis (UC) and Crohn's Disease (CD), is a group of chronic inflammatory disorders. Biologics are indicated for patients failing conventional maintenance therapy with moderate to severe activity. Different routes of administration, intravenous (IV), subcutaneous (SC) or oral have been approved. For chronic diseases such as IBD, some patients may prefer self-administered SC dosing to IV dosing as a less time-intensive and more convenient treatment option. This aims to assess acceptance, safety and satisfaction of transition from IV to SC administration of infliximab (IFX) and vedolizumab (VDZ) in cohort of patients with IBD. Methods: The transition from IV to SC administration was proposed to 91 patients. All patients were given two questionnaire: (a) before the switch, focused on the impact of the IV administration on their life and (b) 8 weeks after the switch focused on the level of satisfaction and onset of adverse event (AE). Data on medical history and treatment was collected from electronic health records. Results: Overall, 91 patients were enrolled for switching from IV to SC therapy. All patients filled the first questionnaire. The IV therapy did not or minimally burden on patients' life in 71% and 15 patients (16%) refused the transition. The main reasons why patients preferred to stay on IV administration were the fear of reducing follow-up visit with IBD staff and the fear of doing the therapy outside the hospital. On the other hand, 76 patients accepted and 8 weeks after the transition they completed the second questionnaire. of these 76, 39 CD and 51 male, 41 (53%) were treated with VDZ and the majority of patients (53%) were at the first line of treatment. Most of patients (67%) did not experience any difficulties in handling the device but "only" the 65% respected the correct time-table of administration. 20% of patients report at least one AE, the most common were erythema, swelling and pain in the injection site. Only the 5% should switch back to IV treament. 8 patients (10%) were switched back to IV administration due to AEs and 1 swaped to Ustekinumab. Conclusion: In this cohort of IBD patients, we found a good acceptance rate (83.5%). The vast majority of patients (95%) was satisfied of transition from IV to SC. Moreover, we reported a good safety profile of SC therapy, AEs were mostly self-limited and local.